Comparative Spectrophotometric Studies of Total Phenolics Content and Antioxidant Capacity Measured by DPPH and ABTS Methods in Green Vegetables - Doganjić, Sofija; Uskoković-Marković, Snežana; Kukić Marković, Jelena; Pavun, Leposava; Janošević Ležaić , Aleksandra (Archives of Pharmacy, 2025)
Modern trends in nutrition imply the daily intake of fresh fruits and vegetables, with the statement that they are important sources of natural antioxidants that protect the body from oxidative stress and can contribute to the prevention of many chronic diseases. In these recommendations, green vegetables with high total phenolics content (TPC) are especially highlighted. However, one must ask whether the high total phenolics content of green vegetables, such as Brussels sprouts, cabbage, broccoli, parsley, borecole and spinach, is a reliable indicator of antioxidant activity for regulating free radicals in the body. The aim of this work is the spectrophotometric determination of TPC of hydromethanol extracts of selected green vegetables and its correlation with their antioxidant potential. For this purpose, DPPH and ABTS radical scavenging tests of extracts were performed. The obtained results indicate that Brussels sprouts and parsley exhibit the highest antioxidative activities, while cabbage extract shows lower values. The Pearson correlation used to test the correlation between the TPC obtained for green vegetable extracts and the results of the DPPH and ABTS tests shows a moderate correlation between TPC and ABTS values, whereas the correlation for TPC and DPPH is statistically significant.
Keywords: green vegetables; antioxidative activities; total phenol content (TPC); DPPH; ABTS